PERSEPSI MASYARAKAT MENGENAI KESYARIAHAN PERBANKAN SYARIAH TERHADAP PREFERENSI MENJADI NASABAH BANK SYARIAH - Natiqotul Khusna; Versiandika Yudha Pratama (Valuasi : Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2021)
This study aims to find out people's perception of sharia banking's preferences to become sharia bank customers. Data collection was conducted by non probability sampling method to the community in Jenggot Village, Pekalongan city through questionnaire. Data analysis using linear regression analysis.  Based on the results of hypothesis testing obtained results that public perception of sharia banking kesyariahan positively and significantly affect the preference to become a customer of sharia banks. Onthe perception side, most of the public agrees that the basis of the existence of sharia banks is by the MUI fatwa on bank interest that is declared haram because it includes usury and the presence of Sharia banking as a solution in avoiding the interest/usury system. However, the public still shows skepticism about the activities and operational systems carried out by Sharia banking to its conformity with sharia principles. Meanwhile, in terms of preferences to become sharia bank customers, the community response has not fully placed its choice on sharia banks. This generally shows that although the public has recognized the presence of Sharia banking as a solution in avoiding the interest/usury system, it does not necessarily encourage people to choose to become sharia bank customers.